Historical Archaeology of the Dente Shrine at Peki, Ghana: Landscapes of Power and Memories of Atlantic Slavery in West Africa - Nutor, B.K.; Gavua, K. (African Archaeological Review, 2023)
Peki is an Ewe-speaking community in present-day southeastern Ghana. In the eighteenth and nineteenth centuries, this community became a hub for the trade in enslaved people. To take charge of the Atlantic economy, the Peki invited the North German Missionary Society to their community in 1847, intending to use them to gain direct access to European merchants on the coast. They also established a franchise of the influential Dente deity of Krachi at Dzake, one of eight Peki settlements. This paper explores the archaeology of the Dente shrine and its role in the historical memory of the Peki community’s entanglements in the Atlantic trade. We employ archaeological, historical, and ethnographic evidence to show how the Peki elites leveraged African indigenous spiritualism to control the post-abolition trade in people. We highlight how contemporary memories of the Atlantic trade in Peki have been constructed through selective processes of remembering and silencing in the face of burgeoning roots and heritage tourism in Ghana. The paper underscores the contradictory roles of an African indigenous religious institution in the complex and syncretic responses to the Atlantic trade in people. It helps us to understand the distinctive power-building strategies that a local community of the West African hinterland adapted to survive in the shadows of expansionist states during the Atlantic trade.
Research Article
Keywords: Atlantic slavery; African indigenous spiritualism; Ethnoarchaeology of indigenous shrines; Social power Memory and memorialization; Community archaeology